2012
DOI: 10.1016/j.jvolgeores.2011.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Migration of tremor locations before the 2008 eruption of Meakandake Volcano, Hokkaido, Japan

Abstract: 7We estimate the locations of three tremor sequences, denoted A, B, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 9 publications
0
33
0
Order By: Relevance
“…The orange-colored side of the rectangle indicates the upper edge of the dike selection of P and S arrivals and confirmed that a similar location shift appeared when they applied the same analysis to VT earthquakes estimated below the PonMachineshiri crater (Figure 8 in Ogiso and Yomogita 2012). In light of this location shift, the source location of the volcanic tremor on November 16 shown in Figure 15 in Ogiso and Yomogita (2012) can be regarded as close to the Pon-Machineshiri crater, which is the assumed location of the centroid of the dike in this study.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…The orange-colored side of the rectangle indicates the upper edge of the dike selection of P and S arrivals and confirmed that a similar location shift appeared when they applied the same analysis to VT earthquakes estimated below the PonMachineshiri crater (Figure 8 in Ogiso and Yomogita 2012). In light of this location shift, the source location of the volcanic tremor on November 16 shown in Figure 15 in Ogiso and Yomogita (2012) can be regarded as close to the Pon-Machineshiri crater, which is the assumed location of the centroid of the dike in this study.…”
Section: Resultsmentioning
confidence: 90%
“…They used the method developed by Battaglia and Aki (2003) and Kumagai et al (2010) to analyze three tremors occurring on September 29, November 16, and November 17-19. According to their results, despite the site amplification correction using coda waves of local earthquakes, the estimated locations of the tremor sources were shifted southward about 1 km from the summit rather than appearing just below the Pon-Machineshiri crater (e.g., Figure 15 in Ogiso and Yomogita 2012). They examined the shift by using the dataset of volcano tectonic (VT) earthquakes that are routinely analyzed by manual The centroid of the dike is fixed below the Akanuma crater, which is the central crater of the Pon-Machineshiri crater area.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations